Internalisasi PAI Multikultural Dalam Menjaga Harmoni Kebhinnekaan Di Tanah Papua - Zainul Fata; Idrus Alhamid; Marwan Sileuw (HUMANISTIKA : Jurnal Keislaman, 2023)
The essence of school is a process to help humans humanize humans so that they respect each other without discrimination. Multicultural values ​​are very important to apply so that intolerant conditions do not occur. This study aims to determine the results of instilling multicultural values ​​through Islamic religious education at SMP NEGERI I Sarmi. This study examines three problems, namely the process of instilling multicultural values, supporting and inhibiting factors and the results of instilling multicultural values. This study uses a qualitative approach with descriptive analytical data analysis. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results of research on instilling multicultural values ​​through PAI, namely, the process of instilling values ​​at SMP NEGERI I Sarmi, uses an active and communicative teaching model with discussion and question and answer methods. Evaluation The results of instilling multicultural values ​​show that in Islamic religious learning students give a positive response to what the teacher conveys in class. Based on the observations of researchers outside the classroom, students have shown multiculturalist attitudes, namely inclusiveness, humanity, tolerance and religious awareness. Key Words: Internalization Model, PAI, Multiculturalism, Harmony, Diversity